The Influence of Education Level and Inequality on Poverty in North Sumatera - Nainggolan, Agustina; Angelica, Marisa; Veliza, Meisya Safa; Sinaga, Mulyati Patresia; Kabeakan, Siat Putri (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This study aims to determine the influence of education level and inequality on poverty in North Sumatra. This research uses annual time series data with a quantitative approach. The results show that partially there is no influence between education level and inequality on poverty in North Sumatra. Simultaneously, there is also no influence between education level and inequality on poverty in North Sumatra. The magnitude of the influence of education level and inequality on poverty in North Sumatra is evident from the coefficient of determination (r square) which is 46%, indicating that education level and poverty significantly affect poverty in North Sumatra.